Special issue “Public policy analysis of integrated water resource management” - Ingold, Karin; Tosun, Jale (Water, 2020)
Public policy analysis is interested in how policies emerge and develop in order to address societal problems. Issues related to water, such as the contamination of surface waters, floods, or plastic pollution in oceans are often highly complex, concern different jurisdictions, and require the collaboration of public and private actors. This complexity is addressed through integrated water management principles. However, these principles give room to open questions such as: what are the main challenges of policy analysis (research and practice) in terms of multi-level actor involvement (politics), cross-sectoral solutions (policies), and new institutional arrangements (polity)? To answer these questions, the seven papers of this Special Issue combine approaches borrowed from policy analysis with principles of Integrated Water Resources Management (IWRM). Each article tackles a complex, water-related problem and collectively, the papers present empirical evidence from case studies located around the world. We learn from all these analyses that adopting a policy perspective helps disentangling the procedural components of IWRM (the involvement of actors, the definition of the appropriate management area, the attribution of competences, etc.) from more substantial ones (like the development of a management plan and the implementation of measures). Addressing cross-sectoral and multi-level challenges is a difficult task, and policy analysis can help shedding light on both, the legitimacy of processes, and the effectiveness of their outputs and outcomes.